The genetics of myelodysplastic syndromes and the opportunities for tailored treatments - Kontandreopoulou, Christina-Nefeli; Kalopisis, Konstantinos; Viniou, Nora-Athina; Diamantopoulos, Panagiotis (Frontiers in Oncology, 2022)
Genomic instability, microenvironmental aberrations, and somatic mutations contribute to the phenotype of myelodysplastic syndrome and the risk for transformation to AML. Genes involved in RNA splicing, DNA methylation, histone modification, the cohesin complex, transcription, DNA damage response pathway, signal transduction and other pathways constitute recurrent mutational targets in MDS. RNA-splicing and DNA methylation mutations seem to occur early and are reported as driver mutations in over 50% of MDS patients. The improved understanding of the molecular landscape of MDS has led to better disease and risk classification, leading to novel therapeutic opportunities. Based on these findings, novel agents are currently under preclinical and clinical development and expected to improve the clinical outcome of patients with MDS in the upcoming years. This review provides a comprehensive update of the normal gene function as well as the impact of mutations in the pathogenesis, deregulation, diagnosis, and prognosis of MDS, focuses on the most recent advances of the genetic basis of myelodysplastic syndromes and their clinical relevance, and the latest targeted therapeutic approaches including investigational and approved agents for MDS.